(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
This research article helps in understanding the optimizationtechnique use in case of computer based databases and mobile databases, etc.Query optimizers normally compile queries into one optimal plan by assumingcomplete knowledge of all cost parameters such as selectivity and resourceavailability. Query optimization is an important skill for SQL developers anddatabase administrators (DBAs). In order to improve the performance of SQLqueries, developers and DBAs need to understand the query optimizer and thetechniques it uses to select an access path and prepare a query execution plan.Mobile technology, IT administrators control the installation process as wellas the configuration policies that determine what optimizations take place peruser or groups of users. Number of mobile internet users is going to be almostdouble till 2011 and the mobile web revolution is all set to come. Industrieslike travel, business and entertainment are getting potential benefit from theinternet mobile search. Mobile search technology in its infancy comprises a lotof possibilities for future. Optimizing websites for mobile browsers now, canput your site ahead of your competitors; providing an incredible profit.